Topical clobetasol propionate 0.025%: a therapeutic dermatologic asset - Singhal, Deepak; Deivasigamani, Revathi; Bhavsar, Bhavik A.; Ganisetti, Lakshmi Sitara; Menghani, Purshotam R.; Majid, Imran; Kukkadapu, Naveen Kumar; Srinivasulu, Gillella; Amol, Sneha; Shah, Rani Sudhir; Wani, Mashkoor Ahmed (International Journal of Research in Medical Sciences, 2022)
Over several decades, topical corticosteroids (TCs) have been used in the treatment of various dermatoses such as psoriasis, contact dermatitis, and eczema, among others. The TCs act by reducing inflammation and irritation after topical application. The therapeutic effect of TCs is bestowed through their diverse biologic properties such as anti-inflammatory, antiproliferative, vasoconstrictive, and antimitotic activity, and its role in the reduction of lymphocyte reactivity, modulation of Langerhans cell expression, cellular and lysosomal membrane stabilization, reduction of recruitment of neutrophils and monocytes, reduction of mast cell density and reactivity, and sensitization of immunoglobulin E. Clobetasol propionate (CP) 0.025% is a class I TC available as a cream formulation. The cream formulation contains half the concentration of conventional CP (0.025%), without the loss of therapeutic potency. The lack of additives such as penetration enhancers (propylene glycol) further prevents cutaneous microbiome alteration. This comprehensive case series covers the potent efficacy and safety of ImpoyzTM (CP) Cream 0.025% in the management of various dermatological disorders.